Patient deprivation and perceived scan burden negatively impact the quality of whole-body MRI. Issue 4 (April 2020) - Evans, R.E.C.; Taylor, S.A.; Kalasthry, J.; Sakai, N.S.; Miles, A.; ,; Aboagye, A.; Agoramoorthy, L.; Ahmed, S.; Amadi, A.; Anand, G.; Atkin, G.; et al.
Abstract : AIM: To evaluate the association between the image quality of cancer staging whole-body magnetic resonance imaging (WB-MRI) and patient demographics, distress, and perceived scan burden. MATERIALS AND METHODS: A sample of patients recruited prospectively to multicentre trials comparing WB-MRI with standard scans for staging lung and colorectal cancer were invited to complete two questionnaires. The baseline questionnaire, administered at recruitment, collated data on demographics, distress and co-morbidity. The follow-up questionnaire, completed after staging investigations, measured perceived WB-MRI scan burden (scored 1 low to 7 high). WB-MRI anatomical coverage, and technical quality was graded by a radiographic technician and grading combined to categorise the scan as "optimal", "sub-optimal" or "degraded". A radiologist categorised 30 scans to test interobserver agreement. Data were analysed using the chi-square, Fisher's exact, t -tests, and multinomial regression. RESULTS: One hundred and fourteen patients were included in the study (53 lung, 61 colorectal; average age 65.3 years, SD=11.8; 66 men [57.9%]). Overall, 45.6% ( n =52), scans were classified as "optimal" quality, 39.5% ( n =45) "sub-optimal", and 14.9% ( n =17) as "degraded". In adjusted analyses, greater deprivation level and higher patient-reported scan burden were both associated with a higher likelihood of having a sub-optimal versus an optimal scan (odds ratio [OR]: 4.465, 95% confidence interval [CI]: 1.454 to 13.709, p =0.009; OR: 1.987, CI: 1.153 to 3.425, p =0.013, respectively). None of the variables predicted the likelihood of having a degraded scan. CONCLUSIONS: Deprivation and patients' perceived experience of the WB-MRI are related to image quality. Tailored protocols and individualised patient management before and during WB-MRI may improve image quality. Highlights: Higher patient social deprivation is associated with poorer WB-MRI scan quality. Higher patient-reported WB-MRI scan burden is associated with poorer scan quality. Tailored protocols and individualised patient management before and during WB-MRI may improve image quality.